2015
DOI: 10.1017/s0332586515000153
|View full text |Cite
|
Sign up to set email alerts
|

The intonation of the Icelandic other-initiated repair expressionsHa‘Huh’ andHvað segirðu/Hvað sagðirðu‘What do/did you say’

Abstract: It has been shown in the literature that cross-linguistically, the other-initiated repair element 'huh' is typically realised with rising intonation. Icelandic has exceptional status in this respect in that it has falling intonation with Ha [haː] 'huh'. The literature claims that it is language-specific interrogative prosody that accounts for this exceptional status of Icelandic. More specifically, it argues that falling intonation is the default for questions in Icelandic and that the other-initiated repair i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The Open-class or unspecified strategy was employed when the students had a problem understanding the message in the previous speaker's utterance, although it was not clear which part of the utterance became the source of non-understanding.This finding mirrors the results of various studies on the employment Open-class OIR in ordinary conversations (Dehé, 2015;Drew, 1997;Enfield et al, 2013;Hayashi & Kim, 2015;Golato & Golato, 2015)Similar to the current study, these studies found that the uses of the interjection "huh" or question word "what" as Open-class OIRs in different languages are ways to address misunderstandings due to problems in hearing the talk.The use of the interrogative pronoun "what" also appeared as a WH-interrogative OIR strategy that the students employed to target specific trouble sources related to the unfamiliar proper names of places, mispronounced words, unclear speech delivery, or L1 words.The employment of WH-interrogatives as an OIR strategy in the current study showed a similar result in other EFL contexts, such as in Iran ( Emrani & Hooshmand, 2019;Fotovatnia & Dorri, 2013) where it is employed to indicate a hearing problem or general understanding of specific trouble sources, such as lexical items, appearing in the prior speaker's utterance.The question words "what", "who", and "when" were used, and the students also used the Partial repeat plus WHinterrogatives OIR strategy to repair trouble sources related to lexical items, such as the unfamiliar proper names of places or mispronunciation of words.By employing these strategies, the students managed to avoid possible breakdowns in the production and understandability of their conversations (Schegloff, 2007).…”
Section: Madar Aleksiussupporting
confidence: 90%
See 1 more Smart Citation
“…The Open-class or unspecified strategy was employed when the students had a problem understanding the message in the previous speaker's utterance, although it was not clear which part of the utterance became the source of non-understanding.This finding mirrors the results of various studies on the employment Open-class OIR in ordinary conversations (Dehé, 2015;Drew, 1997;Enfield et al, 2013;Hayashi & Kim, 2015;Golato & Golato, 2015)Similar to the current study, these studies found that the uses of the interjection "huh" or question word "what" as Open-class OIRs in different languages are ways to address misunderstandings due to problems in hearing the talk.The use of the interrogative pronoun "what" also appeared as a WH-interrogative OIR strategy that the students employed to target specific trouble sources related to the unfamiliar proper names of places, mispronounced words, unclear speech delivery, or L1 words.The employment of WH-interrogatives as an OIR strategy in the current study showed a similar result in other EFL contexts, such as in Iran ( Emrani & Hooshmand, 2019;Fotovatnia & Dorri, 2013) where it is employed to indicate a hearing problem or general understanding of specific trouble sources, such as lexical items, appearing in the prior speaker's utterance.The question words "what", "who", and "when" were used, and the students also used the Partial repeat plus WHinterrogatives OIR strategy to repair trouble sources related to lexical items, such as the unfamiliar proper names of places or mispronunciation of words.By employing these strategies, the students managed to avoid possible breakdowns in the production and understandability of their conversations (Schegloff, 2007).…”
Section: Madar Aleksiussupporting
confidence: 90%
“…Other researchers, such as Cancino's (2015) study with young language learners and Azkarai and Agirre's ( 2016) study with upper-intermediate proficiency learners, investigated whether age, proficiency level, and setting influenced the practice of addressing understanding problems in the interactions of EFL learners. Similar to ESL learners, EFL learners negotiate for meaning during L2 task-based interactions and employ a variety of strategies that help them in the task completion process and when attempting to solve understanding problems during their interactions with peers and teachers.Learning opportunities through classroom interactions are heightened or hindered depending upon the teacher's proper understanding and utilization of how the interaction unfolds moment-by-moment in regard tolearners' turns and utterances based on a particular context of their occurrence (Cancino, 2015) OIR practice is operated through the use of different types of strategies, such as an Open-class (Drew, 1997) OIR, a strategy used with no specification of trouble source in the turn prior to the OIR strategy, when the problem is related to hearing, misunderstanding of talk, or both (Wong & Waring, 2010).Studies on this strategy include Dehé (2015) in Icelandic, Enfield et al, (2013) in mundane conversations across several languages, Fotovatnia and Dorri (2013) in Iranian EFL learners conversations, Golato and Golato (2015) in German and French, and Hayashi and Kim (2015) in Japanese and Korean. These studies found that the Openclass OIR strategy is represented by the interrogative pronoun 'what' or an interjection 'huh' or "yeah", which are used either in isolation or in combination with other OIR types, such as repetition, to address different kinds of trouble sources.…”
Section: Repair Practice In the Classroom Conversations Of Indonesian Efl Studentsmentioning
confidence: 99%
“…The data used here are taken from a map task study carried out by the author of the present paper in Iceland during the months of October 2013 to January 2014 and May–June 2014, and in Manitoba, Canada in August 2014 (see also Dehé 2015). The map task has the advantage of eliciting quasi-spontaneous speech produced in an interactive discourse while at the same time allowing for i) some control over the lexical elements used by the participants and thus the segmental make-up of target elements, ii) comparability between groups of speakers, and iii) control over sociolinguistic factors such as age, regional origin, and the like.…”
Section: Methodsmentioning
confidence: 99%
“…The data used here are taken from the Icelandic map task corpus collected in Iceland and in Manitoba, Canada, in 2013-2014 (Dehé 2015(Dehé , 2018.…”
Section: Data and Analysismentioning
confidence: 99%